Solar a novel - McEwan, Ian (Vintage Books, 2011)
Michael Beard is a Nobel prize winning physicist whose best work is behind him. Trading on his reputation, he speaks for enormous fees, lends his name to the letterheads of renowned scientific institutions, and half-heartedly heads a government-backed initiative tackling global warming. While he coasts along in his professional life, Michael's personal life is another matter entirely. His fifth marriage is crumbling under the weight of his infidelities. But this time the tables are turned: his wife is having an affair, and Michael realizes he is still in love with her.